EFEKTIFITAS KONSUMSI TABLET FE DITAMBAH JUS NAGA MERAH DAN JUS TOMAT TERHADAP HEMOGLOBIN IBU HAMIL ANEMIA - Zuraida Zuraida; Husnawati Husnawati (Universitas Fort de Kock Bukittinggi, 2022)
Anemia in pregnancy is a decrease in hemoglobin levels. This is caused by a lack of iron consumption. The prevalence of anemia in Nilam Sari Health Center Bukittinggiwas 30% in 2017. The aim of the study was to determine the effectiveness of consumption of Fe tablets plus red dragon fruit juice compared to Fe tablets plus tomato juice to increase hemoglobin in pregnant women with anemia.Type of research was True-experiment with the Two Group Pretest Posttest design. The research was conducted at Nilam Sari Public Health Center on April 27 - May 10 2018 to 20 anemia pregnant women with purposive sampling technique. Statistical tests were carried out by the Dependent T-Test. The results of group I study showed an increase in hemoglobin levels of pregnant women before and after the intervention of 0.98. Statistical test results p value = 0,000 (p <0,05), while group II is 1,45. Statistical test results p value = 0,000 (p <0,05) concluded Fe tablets plus red dragon fruit juice and Fe tablets plus tomato juice effectively increase hemoglobin levels. The administration of Fe tablets plus red dragon fruit juice and Fe tablets plus tomato juice is effective for increasing hemoglobin levels. It is expected that the caregiver in the Health Center will provide health education about natural therapies that can help increase hemoglobin levels in anemic pregnant women, one of them is consumption of Fe tablets plus red dragon fruit juice and Fe tablets plus tomato juice.Keywords: Fe tablet, dragon fruit, tomato fruit, anemia, hemoglobin increase